The Cosmic Chemical Evolution Histories of Spiral Galaxies - Greener, Michael John (2023)
Spiral galaxies have always been of particular interest to astronomers ever since it was discovered that our own galaxy, the Milky Way, is itself a spiral. Although long-slit spectroscopy of galaxies has been available for over half a century, the recent advent of large-scale integral field unit surveys such as SDSS-IV MaNGA means that spatially resolved spectroscopic observations are now available for thousands of nearby spiral galaxies. In this thesis, we will use data from the MaNGA survey to investigate the fundamental properties and the chemical evolution of spiral galaxies.